2021
DOI: 10.1186/s12888-021-03377-x
|View full text |Cite
|
Sign up to set email alerts
|

Borderline personality disorder and adolescent suicide attempt: the mediating role of emotional dysregulation

Abstract: Background Emotional dysregulation seems to be a core feature of Borderline Personality Disorders (BPD). In addition, recent research in the adolescent population has shown that suicidal behaviours have been associated with maladaptive strategies of emotion regulation. Methods This study examined the relative contributions of emotional dysregulation to suicide attempt history in a clinical sample of borderline adolescents. Data were analyzed from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 76 publications
(83 reference statements)
1
16
0
1
Order By: Relevance
“…33 Targeting the prevalent emotional dysregulation and international difficulties in cluster B populations by appropriate psychological interventions should be highlighted. 34 Notably, reattempting attempts occurred within weeks (8 days [2.5, 23]), agreeing to the Danish database the cumulative rates of reattempting suicide were particularly high within the first week of the index attempt. 35 Preventive efforts need to target the period close to discharge from the ED.…”
Section: Reattempting Suicidesupporting
confidence: 65%
See 1 more Smart Citation
“…33 Targeting the prevalent emotional dysregulation and international difficulties in cluster B populations by appropriate psychological interventions should be highlighted. 34 Notably, reattempting attempts occurred within weeks (8 days [2.5, 23]), agreeing to the Danish database the cumulative rates of reattempting suicide were particularly high within the first week of the index attempt. 35 Preventive efforts need to target the period close to discharge from the ED.…”
Section: Reattempting Suicidesupporting
confidence: 65%
“…These populations warrant attention in the suicide prevention strategy 33 . Targeting the prevalent emotional dysregulation and international difficulties in cluster B populations by appropriate psychological interventions should be highlighted 34 …”
Section: Discussionmentioning
confidence: 99%
“…(9) Regarding emotional dysregulation, a study conducted with adolescent girls with borderline personality disorder identified that participants who had greater difficulty in regulating their emotional experiences were at greater risk for making a suicide attempt. (10) Self-injuries in adolescents were also identified by teachers in the school environment. Data from the Brazilian Ministry of Health point out that, nationally, the age group between 10 and 19 years old appears in second place in the occurrences of self-injury, and this practice is considered a predictive factor for future suicide attempts.…”
Section: Discussionmentioning
confidence: 99%
“…This is absolutely true as it could be found in high levels of depression based on symptom hierarchy [56]. However, for those exhibiting borderline personality, suicidality may be present in a milder form of depression [57,58]. Many studies did not exclude the suicidal item from the whole depressive questionnaire, rendering a falsely inflated correlation between depressive symptoms and suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%